2015
DOI: 10.1186/s12912-014-0054-6
|View full text |Cite
|
Sign up to set email alerts
|

Shift work to balance everyday life - a salutogenic nursing perspective in home help service in Sweden

Abstract: BackgroundNurses in Sweden have a high absence due to illness and many retire before the age of sixty. Factors at work as well as in private life may contribute to health problems. To maintain a healthy work–force there is a need for actions on work-life balance in a salutogenic perspective. The aim of this study was to explore perceptions of resources in everyday life to balance work and private life among nurses in home help service.MethodsThirteen semi-structured individual interviews and two focus group in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 60 publications
2
23
0
1
Order By: Relevance
“…Studies with a focus on salutogenic experiences at work have shown that meaningfulness is an important workplace-related health resource (Agosti, Andersson, Ejlertsson, & Janl€ ov, 2015;Brings en et al, 2012;Nilsson et al, 2012). For instance, Nilsson et al (2012) found that aspects such as confirmation through encounters with other people were related to bringing a sense of meaningfulness.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with a focus on salutogenic experiences at work have shown that meaningfulness is an important workplace-related health resource (Agosti, Andersson, Ejlertsson, & Janl€ ov, 2015;Brings en et al, 2012;Nilsson et al, 2012). For instance, Nilsson et al (2012) found that aspects such as confirmation through encounters with other people were related to bringing a sense of meaningfulness.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently, previous studies have shown that younger age has strong associations with more social activities, which could prevent depression [34]. For the elderly, depressive symptoms can spontaneously appear when social support provided by work disappears and their children are unable to provide support for them in time [35]. …”
Section: Introductionmentioning
confidence: 99%
“…Well-managed shift work has been shown to improve employees' sense of work-life balance and their well-being (Agosti et al, 2015), which could ultimately affect the quality of care and organisational performance. However, the employees' perception of how shift work affects their lives was a much stronger predictor of their PWBW.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%